Factors driving the intention to adopt a tobacco-free policy among employees in a public higher education institution - Abdul Manan, Kamaruzzaman; Ahmad, Che Mahzan; A.Manaf, Aini Maznina; Mohd Samin, Ahmad Shalihin (IIUM Press, International Islamic University Malaysia, 2019)
Due to their role as a centre of knowledge and character development, public higher education institutions serve as the best platform for emphasising health communication messages and promoting a healthy lifestyle. Higher educational institutions’ employees should have good physical and mental health to enable them to demonstrate good values to the students. Thus, the social cognitive theory (SCT) was specifically selected to take a close look at how a conducive environment and knowledge influence employees’ intention towards the tobacco-free policy. This study used the partial least squares (PLS) and structural equation modelling (SEM) software to examine factors influencing the adoption of tobacco-free policy among employees in a Malaysian higher education institution. It also measured the impact of workplace health promotion on employees’ intention to comply with tobacco cessation regulations. Statistical results confirmed that all three constructs of employees’ environment, self-efficacy, and knowledge have a significant influence on employees’ intention to adopt the tobacco-free policy. The results of the study contribute to a better understanding of the effectiveness of higher education institutions’ tobacco-free policy in Malaysia. The findings are useful for policymakers, higher education institutions, and practitioners in enhancing tobacco cessation policy in Malaysia. Limitations and suggestions for future research are also included in this paper.